The Impact of Intense Physical Exercise on the Hormonal Profile, Metabolic Functions and Immune Response in Patients with Hashimoto’s Disease – A Literature Review - Skórka, Aleksandra; Dokurno, Małgorzata; Kasperek, Rafał; Matyla, Paulina; Brankowska, Karolina (Quality in Sport, 2026)
Background: Hashimoto's disease is the most common cause of hypothyroidism. While moderate exercise is recommended as a non-pharmacological component of treatment, the body's response depends strongly on the intensity and load of exercise. Aim: To review the impact of intense physical exercise on the hormonal, metabolic, and immune profiles of patients with Hashimoto's disease Material and methods: A review of clinical and population studies evaluating physiological and immune responses to various exercise intensities in Hashimoto’s disease Results: Studies reveal a “physical activity paradox”. Moderate exercise lowers TSH and antibody levels. However, extreme exertion (e.g., heavy occupational work or >1,520 active mins/week) exacerbates autoimmunity. Exhaustive exercise increases the risk of overt hypothyroidism, raises TSH and anti-TPO antibodies, and decreases free hormones (fT4, fT3). It also induces a "low T3 syndrome" during recovery, triggers transient immune dysfunction, and worsens pathological exercise intolerance, which significantly increases the risk of life-threatening rhabdomyolysis. Conclusions: Intensive, exhaustive training in uncontrolled Hashimoto's patients is highly contraindicated, causing endocrine breakdown and inflammation. Only precisely dosed, moderate aerobic exercise with absolute respect for prolonged recovery times is recommended.